Challenges and Opportunities of Islamic Branding on Global Marketing: A Conceptual Study - Arizal Hamizar; Mohammad Hanafi Holle; Syed Ismail Syed Mohamad (Fakultas Studi Islam Universitas Islam Kalimantan Muhammad Arsyad Al Banjary, 2023)
This study explores the challenges and opportunities of creating effective Islamic branding strategies in the motivation & preferences of Muslim customers. The study begins by reviewing the existing literature on Islamic branding and the factors that have contributed to its emergence. Next, the study examines the challenges faced by companies in creating effective Islamic branding strategies, including issues related to authenticity, transparency, and cultural sensitivity. Finally, the study explores the opportunities available to companies in the Islamic branding market, including the potential for growth and the ability to reach a broader market of ethical and socially conscious consumers. The findings suggest that while the Islamic branding market offers significant opportunities for companies, it also poses significant challenges. To create effective Islamic branding strategies, companies must be authentic and transparent in their adherence to Islamic values, while being culturally sensitive and aware of Muslim consumers' diverse needs and preferences. Additionally, companies must recognize that the success of Islamic branding is not solely dependent on the appeal to Muslim consumers, but also on the ability to appeal to a broader market of ethical and socially conscious consumers. Penelitian ini menggali tantangan dan peluang dalam menciptakan strategi Islamic branding yang efektif dalam motivasi dan preferensi pelanggan Muslim. Penelitian ini dimulai dengan meninjau literatur yang ada tentang branding Islami dan faktor-faktor yang telah berkontribusi pada kemunculannya. Selanjutnya, penelitian ini mengkaji tantangan yang dihadapi oleh perusahaan dalam menciptakan strategi branding Islami yang efektif, termasuk masalah-masalah terkait dengan otentisitas, transparansi, dan sensitivitas budaya. Terakhir, penelitian ini mengeksplorasi peluang yang tersedia bagi perusahaan di pasar branding Islami, termasuk potensi pertumbuhan dan kemampuan untuk mencapai pasar yang lebih luas dari konsumen yang etis dan peduli sosial. Temuan penelitian menunjukkan bahwa meskipun Islamic branding menawarkan peluang signifikan bagi perusahaan, ia juga menimbulkan tantangan yang signifikan. Untuk menciptakan strategi branding Islami yang efektif, perusahaan harus menjadi otentik dan transparan dalam pematuhan nilai-nilai Islami mereka, sambil sensitif secara budaya dan menyadari kebutuhan dan preferensi yang beragam dari konsumen Muslim. Selain itu, perusahaan juga harus menyadari bahwa kesuksesan branding Islami tidak semata-mata bergantung pada daya tarik kepada konsumen Muslim, tetapi juga pada kemampuan untuk menarik pasar yang lebih luas dari konsumen yang etis dan peduli sosial.